القاعدة: هل الخاص مقدم على العام؟ وأثرها على الفروع الفقهية، دراسة نظرية تطبيقية من خلال فتح القدير لابن الهمام : Is “Kẖāṣ” preferred over “ʿām”: An applied Study of this Maxim in the light of fatḥ al-qadīr by ibn al-humām - Khan, Muhammad Sarfraz (الدراسات الإسلامية, 2021)
The article aims to discuss opinions of experts of the principles of Islamic Jurisprudence regarding the Jurisprudential Maxim: “Is “Kẖāṣ” preferred over “ʿām” in Islamic Jurisprudence”? Which is the most important maxims in Islamic jurisprudence. Islamic jurisprudence and its principles are two most important interlinked disciplines of Islamic studies, which ordinarily studied separately. Fiqh (Islamic Law considered the jurists Law, which is the outcome of Jurist’s interpretation of the texts of Quran and Sunnah. The Science of uṣūlu al-fiqh comprises of philosophy and principles/maxims. The Jurisprudential Maxims are the ultimate tool through which the process of interpretation is conducted. The Islamic Law is not given to man ready-made, to be passively received and applied; rather it is to be actively construed primarily on the basis of Quran and Sunnah and through the application of the principles of interpretation incorporated in Islamic Jurisprudence. The process of interpretation, however, based upon the glorious principles, which are known as jurisprudential maxims, or principles of interpretation, scattered in the classical literature of Islamic Jurisprudence. The study will primarily discuss the meaning and different phrases of the maxim along with mentioning the opinions of Jurists about it. Secondly, as the Classical Fiqh book of renowned ḥanafī Jurist Kamal ibn al-humām namely: fatḥ al-qadīr is selected as case study; practical applications out of the book will also be discussed, so that the scope and significance of this very maxim may be understood in a better way.